1995
DOI: 10.1007/bf02285184
|View full text |Cite
|
Sign up to set email alerts
|

Anismus as a marker of sexual abuse

Abstract: Anorectal manometry was performed in 40 women, who consulted for functional disorders of the lower gastrointestinal tract and had been sexually abused. Anismus, defined as a rise in anal pressure during straining, was observed in 39 of 40 abused women, but in only six of 20 healthy control women (P < 0.0001). Other parameters of anorectal manometry were compared with those observed in another control group composed of 31 nonabused women but with anismus, as well as the group of healthy controls. A decreased am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(9 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Anismus is a form of functional obstructed defecation and can cause constipation [18] and painful defecation. It is more common in women than in men, and sometimes is associated with sexual abuse [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Anismus is a form of functional obstructed defecation and can cause constipation [18] and painful defecation. It is more common in women than in men, and sometimes is associated with sexual abuse [19]. …”
Section: Discussionmentioning
confidence: 99%
“…177 Uncontrolled studies have reported sexual abuse in 22% of women with FDD, and 40% of women with functional lower gut disorders, including FDD. 140,178 …”
Section: F3 Functional Defecation Disordersmentioning
confidence: 99%
“…The etiology of this dysfunction remains unknown. Nevertheless an association with sexual abuse is suggestive of a psychologic basis [20] , [21] . To our knowledge there were not studies comparing the frequency of this syndrome regarding gender.…”
Section: Discussionmentioning
confidence: 99%